Effects of Moringa oleifera Extract as an Immunomodulator of Lymphocyte Cells and Macrophages in BALB/c Mice Infected with Plasmodium berghei - Jaya, Putu Khrisna Dharma; Apsari, Putu Indah Budi; Dewi, Pande Made Alitta Cantika Putri Nadya; Laksemi, Dewa Ayu Agus Sri; Sutarta, I Ketut Cahyadi Adi Winata (Folia Medica Indonesiana, 2023)
Highlights: 1. This study assessed the immunomodulatory potential of Moringa oleifera, which may serve as a natural source for antimalarial treatment. 2. Moringa oleifera extract can act as an immunomodulator due to its suppressive effect on Plasmodium berghei infection. Abstract Malaria is an infectious disease caused by protozoa of the genus Plasmodium. In Indonesia, this disease remains a health concern that must be resolved. Due to its high prevalence in eastern Indonesia, it is a challenge to eradicate this disease. Moringa oleifera contains various substances that are believed to have antimalarial activity. This study aimed to determine the effectiveness of Moringa oleifera leaf extract in increasing immune cells and eradicating parasites by using mice infected with Plasmodium berghei. The research was conducted in vivo on BALB/c strain mice (n=40) that were already infected with Plasmodium berghei. Moringa oleifera leaf extract at 25%, 50%, and 75% concentrations was administered orally every day to the mice, while a peripheral blood smear was performed to evaluate parasitemia levels and macrophage activation. A complete blood count was also performed after all tests on the mice were completed. Statistical analysis was performed using the one-way analysis of variance (ANOVA) test with a=0.05 and 95% confidence interval (CI). The results showed that the administration of Moringa oleifera leaf extract at 25%, 50%, and 75% concentrations caused varying degrees of parasitemia compared to the negative group (p<0.05). The group that received the extract at 50% concentration differed significantly from the control groups in the number of activated macrophages. The results of the complete blood count indicated immunomodulatory effects through the presence of diverse immune cell types. In conclusion, Moringa oleifera leaf extract suppresses Plasmodium berghei infection and enhances immune cell stimulation.